1999
DOI: 10.1128/mcb.19.2.1438
|View full text |Cite
|
Sign up to set email alerts
|

p73 Function Is Inhibited by Tumor-Derived p53 Mutants in Mammalian Cells

Abstract: The p53 tumor suppressor protein, found mutated in over 50% of all human tumors, is a sequence-specific transcriptional activator. Recent studies have identified a p53 relative, termed p73. We were interested in determining the relative abilities of wild-type and mutant forms of p53 and p73␣ and -␤ isoforms to transactivate various p53-responsive promoters. We show that both p73␣ and p73␤ activate the transcription of reporters containing a number of p53-responsive promoters in the p53-null cell line H1299. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
332
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(355 citation statements)
references
References 69 publications
19
332
3
Order By: Relevance
“…The first is the interplay between p53 and p63/p73: although there is little evidence of heterotetrameric formation of p53-p63 dimers (Davison et al, 1999), several reports have indicated that p63/p73 have an increased affinity for p53 missense mutants (Di Como et al, 1999;Strano et al, 2000;Gaiddon et al, 2001). Specifically, p63 was reported to associate with the p53 mutants of HaCaT cells (Gaiddon et al, 2001).…”
Section: Activation Of Klf4 By Mutant P53mentioning
confidence: 99%
“…The first is the interplay between p53 and p63/p73: although there is little evidence of heterotetrameric formation of p53-p63 dimers (Davison et al, 1999), several reports have indicated that p63/p73 have an increased affinity for p53 missense mutants (Di Como et al, 1999;Strano et al, 2000;Gaiddon et al, 2001). Specifically, p63 was reported to associate with the p53 mutants of HaCaT cells (Gaiddon et al, 2001).…”
Section: Activation Of Klf4 By Mutant P53mentioning
confidence: 99%
“…Whatever the structural basis for the association of mutant p53 with its homologues, several studies have documented decreased transcriptional activities of p63/p73 and their ability to induce growth suppression and apoptosis when in the presence of mutant p53 (Di Como et al, 1999;Marin et al, 2000;Strano et al, 2000Strano et al, , 2002Gaiddon et al, 2001;Bergamaschi et al, 2003). Importantly, these studies have indicated a good correlation between the efficiency of binding to and inactivation of p63/p73 by mutant p53.…”
Section: Mutant P53 Interactions With P63 and P73 Have Functional Outmentioning
confidence: 99%
“…Despite this it has been shown that a number of p53 mutants can associate with either p73 or p63 as evidenced by co-immunoprecipitation assays when they are either ectopically or endogenously expressed (Di Como et al, 1999;Marin et al, 2000;Strano et al, 2000Strano et al, , 2002Gaiddon et al, 2001;Bergamaschi et al, 2003;Irwin et al, 2003). Both 'conformation' mutants (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…57 Moreover, it has recently been shown that several tumour-derived mutants of p53 that are often retained in cancer are able to bind and inactivate p73, thereby circumventing the necessity to mutate p73 per se. 58 This process reduces chemosensitivity and adds more weight to the fact that E2F-1-induced apoptosis is an important tumour-suppressive mechanism as well a prognostic indicator of therapeutic success. 59,60 Another mechanism of E2F-1-induced apoptosis is via the inhibition of antiapoptotic signalling.…”
Section: A Role In Cancermentioning
confidence: 99%